Scott and Amundsen - Honda, Katuiti (The Asahi-Shinbun, 1999)
Publication Title: Complete collection of Katsuichi Honda
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Miljøgifter og radioaktivitet i norsk fauna : inkludert Arktis og Antarktis - Knutzen, Jon; Fjeld, Eirik; Hylland, Ketil; Killie, Barbro; Kleivane, Lars; Lie, Elisabeth; Nygård, Torgeir; Savinova, Tatiana; Skåre, Janneche Utne; Aanes, Karl Jan (Direktoratet for naturforvaltning, 1999)
Publication Title: Utredning for DN
Keywords: Antarktis; dyreliv; forurensning; miljøgifter; polarområdene; radioaktivitet; toksikologi; zoologi

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Strategi for norsk forskning i Antarktis - forskningsråd, Norges (Norges forskningsråd, 1997)
Keywords: Antarktis; Antarktistraktaten; Norge; forskning; forvaltningsansvar; miljøendringer; polarområdene

Dagboksnotater fra Sydpolen - Hassel, Sverre (Vågemot miniforl., 1997)
Publication Title: Sydpol-serien
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Governing the Antarctic : the effectiveness and legitimacy of the Antarctic Treaty System - Støkke, Olav Schram (ed.); Vidas, Davor (ed.) (Cambridge University Press, 1996)
Keywords: Antarktis; Antarktistraktaten 1959; internasjonal politikk; polarområdene; politikk

Background to the establishment of Norsk Polarinstitutt : postwar scientific and political agendas - Friedman, Robert Marc (Umeå university, 1995)
Publication Title: The Northern Space. The International Research Network on the History of Polar Science, Working Paper
Keywords: Antarktis; Norsk Polarinstitutt; historie; internasjonal; polarområdene; politikk

Moje życie polarnika - Amundsen, Roald; Thylwe, Halina (Iskry, 1993)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Environmental radioactivity in the Arctic and Antarctic - Holm, Elis (red.); Strand, Per (red.) ("International Conference on Environmental Radioactivity in the Artic and Antarctic organized by Norwegian Radiation Protection Authority, Norway and Department of Radiation Physics, Lund University, Sweden., 1993)
Keywords: Antarktis; miljøforurensing; polarområdene; radioaktivitet

The Antarctic treaty system in world politics - Jørgensen-Dahl, Arnfinn (Red.); Østreng, Willy (Red.) (Macmillan in association with The Fridtjof Nansen Institute, 1991)
Keywords: Antarktis; Antarktistraktaten; forvaltning; havrett; internasjonalt samarbeid; miljø; naturressurser; polarområdene; politikk; ressurser; rett

Perspektiver for norsk forskning i Antarktis : langtidsplan for norsk Antarktis-forskning, høringsutkast av kapittel 6: framtidig norsk forskning - Omholt, Anders; Nygard, Jarle (Nasjonal komite for miljøvernforskning, NAVF, 1991)
Keywords: Antarktis; Norge; glasiologi; klima; marinøkologi; miljøforskning; polarforskning; polarområdene

Adaptations to alpine and polar environments in insects and other terrestrial arthropods - Sømme, Lauritz; Block, William (Insects at low temperature, 1991)
Keywords: Antarktis; ekspedisjoner; insekter; kuldetoleranse; polarområdene; virvelløse dyr

Nankyoku ten - Amundsen, Roald; Nakada, Osamu (Dorufin Press, 1990)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Oversikt over naturområder og forekomster i Norge og polarområdene som er fredet eller vernet pr. 1. januar 1985 (Miljødepartementet, 1985)
Pages: 96 s. Place: Oslo
Keywords: Bouvetøya; kultur; miljøvern; naturvern; polarområdene

Norge og den sovjetiske polarforskning i nord og sør - Magnus, Morten H (Farmand, 1983)
Keywords: Antarktis; ekspedisjoner; polarforskning; polarområdene

Amundsen's route to the South Pole - Drewry, David John; Huntford, Roland (Polar Record, 1979)
Publisher: Cambridge University Press
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Scott and Amundsen - Huntford, Roland (Hodder & Stoughton, 1979)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Naturressurser i Antarktis: av særlig interesse for Norge - Mobæk, Are; Østgård, Jon; Børset, Erik; Karlsen, Bernt Stilluf; Larsen, Thor (Miljøverndepartementet, 1979)
Keywords: Antarktis; polarområdene; ressurser

Sydpolen - Amundsen, Roald; Lindberg, Odd F (Niloe, 1978)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Polarområdenes økosystemer - Larsen, Thor (1978)
Pages: 8 s. Place: [Oslo]
Keywords: Antarktis; polarområdene; økologi

Norsk polarpolitikk ut av tåkeheimen - Leistad, Geirr I (Farmand, 1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene; polarpolitikk

Global glacier mass balance variations during the past 300 years - Orheim, Olav (Arctic Institute of North America, 1977)
Pages: 667-681 Publication Title: Polar Oceans Place: McGill University, Montreal, Canada
Keywords: Antarktis; glasiologi; is; isbreer; klimaendringer; konferanse; polarområdene; stratigrafi; symposium

Antarktis - Antonsen, Per (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ekspedisjoner; polarområdene

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene

Svalbard - Jan Mayen - The Antarctic Possessions (Utenriksdepartementet, 1973)
Publication Title: Norway Information Volume: UDA 297/73 Place: Oslo
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Svalbard, Jan Mayen, antarktische Besitzungen - Gjelsvik, Tore (1969)
Publisher: Utenriksdepartementet Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Sætrykk
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Arktis og Antarktis : aktuelle problemstillinger - Sollie, Finn (Internasjonal politikk, 1968)
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

En del sovjetiske forskningsinstitusjoner, med særlig vekt på de som arbeider med oppgaver i arktiske og antarktiske strøk - Heintz, Natascha ([Norsk Polarinstitutt], 1965)
Pages: 18 s. Place: Oslo
Keywords: Antarktis; forskning; polarområdene; vitenskap

Man in Antarctica - Rodahl, Kaare (Science in Antarctica. Part 1: The Life sciences in Antarctica, 1961)
Keywords: Antarktis; ekspedisjoner; forskning; fysiologi; kuldetoleranse; medisin; polarområdene

Main events in the history of antarctic exploration - Bogen, Hans (The Norwegian Whaling Gazette, 1957)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Thorshavn ekspedisjoner; geografi; historie; oppdagelsesreiser; polarområdene

Some recent work on polar navigation - Foster, L R R (The Journal of The Institute of Navigation, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; navigasjon; polarområdene

Flyplasser på snø og is - Pedersen, Gunnar S. (Teknisk ukeblad : Norges fremste på teknologi, 1948)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY) 1957/1958; ekspedisjoner; logistikk; polarområdene

Vår ishavsflåte og selfangsten : ishavsskutenes innsats i arktisk og antarktisk forskning - Hansen, Rolf (Vår Flåte, 1944)
Keywords: Sørishavet; ekspedisjoner; forskning; polarområdene; selfangst

Norges livsrom - Hoel, Adolf (Det nye Norge, 1944)
Publisher: <s.n.> Place: Oslo
Keywords: Antarktis; hvalfangst; internasjonal politikk; polarområdene; økonomi

De sydpolare områder - Smedal, Gustav (Suverenitetspørsmål i polarområdene, 1942)
Keywords: Antarktis; internasjonal; polarområdene; politikk; rett

Det nye norske land i Antarktis - Isachsen, Fridtjov (Mellanfolkligt samarbete, 1939)
Keywords: Dronning Maud Land; Norge; geografi; hvalfangst; internasjonal politikk; polarområdene

The new Norwegian dependency in the Antarctic - Isachsen, Fridtjov (Le Nord : Revue internationale des pays du nord = International review of the northern countries, 1939)
Keywords: Dronning Maud Land; Norge; geografi; hvalfangst; internasjonal politikk; polarområdene

Juznyj poljus (Sydpolen) - Amundsen, Roald (Molodaja Gvardija, 1937)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Sledge Dogs on Amundsen's South Polar Journey - Hanssen, Helmer (Polar Record, 1937)
Publisher: Cambridge University Press
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

The South Pole attained: Amundsen in the Fram - Hayes, Gordon J (The conquest of the South Pole : antarctic exploration 1906-1931, 1932)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; polarområdene

The work of the whalers and the discovery committee - Hayes, Gordon J (The conquest of the South Pole : antarctic exploration 1906-1931, 1932)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; Odd I; ekspedisjonen; ekspedisjoner; forskning; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene

Bemerkungen zu K.Lampe: Versuch einer politischen Geographie der Polargebiete - Braastad, Johan (Geographischer Anzeiger, 1931)
Keywords: Antarktis; geografi; polarområdene; politikk

Erwerb von Staatshoheit über Polargebiete - Smedal, Gustav (Gräfe und Unzer, 1931)
Publication Title: Öffentlich-rechtliche Vorträge und Schriften
Keywords: Antarktis; internasjonal; jus; polarområdene; politikk

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Mein Leben als Entdecker - Amundsen, Roald; Běhounek, František; Schwarz, Georg (E.P. Tal, 1929)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Elämäni ja tutkimusretkeni - Amundsen, Roald (Werner Söderström, 1928)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Wo das Südlicht flammt : Scotts letzte Südpol-Expedition und was ich dabei erlebte - Gran, Tryggve; Mohr, Adrian (Otto Uhlmann, 1928)
Publication Title: Hvor sydlyset flammer
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

Paa Hvalfangst i Sydishavet : den norske Hvalfangerekspedition 1923-24 - Villiers, Alan (Pio, 1927)
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst; pelagisk; polarområdene

Zur grossen Eismauer des Südpols : eine Fahrt mit norwegischen Walfischfängern - Kohl-Larsen, Ludwig (Strecker und Schröder, 1926)
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst; pelagisk; polarområdene; zoologi

Whaling in the frozen south : being the story of the 1923-24 Norwegian whaling expedition to the Antarctic - Villiers, Alan (Hurst & Blackett, 1925)
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst; pelagisk; polarområdene

To the frozen south - Villiers, Alan (Davies Brothers Ltd, 1924)
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst; pelagisk; polarområdene

Die Eroberung des Südpols : die norwegische Südpolfahrt mit dem Fram 1910-1912 : Erster Band - Amundsen, Roald; Klaiber-Gottschau, Pauline (Lehmann, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Die Eroberung des Südpols : die norwegische Südpolfahrt mit dem Fram 1910-1912 : Zweiter Band - Amundsen, Roald; Klaiber-Gottschau, Pauline (Lehmann, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Plan for en polarfærd 1910-1917. Foredrag tirsdag den 10.november 1908 med efterfølgende bemerkninger af professorene Mohn og Nansen - Amundsen, Roald (Det Norske Geografiske Selskabs Aarbok, 1909)
Publisher: Aschehoug Place: Kristiania
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser; polarområdene

Südwärts! : die Expedition von 1893-1895 nach dem südlichen Eismeere - Bull, Henrik Johan (Haessel, 1904)
Keywords: Henrik Johan Bull; Sydpolen; Sørishavet; ekspedisjoner; oppdagelsesreiser; polarområdene